Roads and forest edges facilitate yellow fever virus dispersion. Issue 1 (6th October 2021) - Ribeiro Prist, Paula; Reverberi Tambosi, Leandro; Filipe Mucci, Luís; Pinter, Adriano; Pereira de Souza, Renato; de Lara Muylaert, Renata; Roger Rhodes, Jonathan; Henrique Comin, César; da Fontoura Costa, Luciando; Lang D'Agostini, Tatiana; Telles de Deus, Juliana; Pavão, Mônica; et al.
Abstract: Landscape connectivity is important for a wide range of ecological processes, including to disease spread, once it describes the degree to which landscapes facilitate or impede vector and hosts dispersion. Understanding connectivity is extremely important to identify where pathogens can move, and at what speed, allowing the organization of vaccination campaigns or other preventive measures. To better understand the effects of landscape connectivity on yellow fever virus (YFV) dispersion in Brazil, we used a network approach and modelled the movement of non‐human primates' cases, the so‐called epizootic events, over time. The networks consider each epizootic event as a node and the dispersion between nodes as links. Those links were established considering, respectively, the date of each epizootic event, the distance among the nodes and the permeability of the landscape between each pair of nodes. Our results demonstrated that on average YFV dispersed 1.42 km/day, with the largest movement being 6.9 km/day. Dispersions were longer in summer (1.2 km/day) than in winter (0.22 km/day). Most dispersal movements occurred up to 1 km/day (71%) and within a week after the arrival of the virus in the source node (73%), except in winter, where dispersions occurred within a period of up to 20 days. The best model indicates that YFV disperses mainly through roads adjacent to forest areas, and along forest edges (within a range of 100 m) in interface with agricultural areas, water and forestry areas. Core areas of urban, agricultural and forest regions were important barriers for virus movement. Synthesis and applications . Through landscape connectivity analyses, we provided here the first evidence that highly fragmented landscapes with a wide road network and large densities of forest edges facilitate yellow fever virus propagation, and that the maintenance of large blocks of forest can help to inhibit this spread. These results can contribute to guide forest restoration and landscape management actions in order to amplify health benefits related to restoration projects, in addition to their benefits for biodiversity conservation and climate change mitigation. Abstract : Through landscape connectivity analyses, we provided here the first evidence that highly fragmented landscapes with a wide road network and large densities of forest edges facilitate yellow fever virus propagation, and that the maintenance of large blocks of forest can help to inhibit this spread. These results can contribute to guide forest restoration and landscape management actions in order to amplify health benefits related to restoration projects, in addition to their benefits for biodiversity conservation and climate change mitigation. Resumo: A conectividade da paisagem é importante para uma ampla gama de processos ecológicos, inclusive para a dispersão de doenças, uma vez que descreve o grau em que as paisagens facilitam ou impedem a dispersão de vetores e hospedeiros. Entender essa conectividade é extremamente importante para identificar por onde os patógenos podem se mover, e a que velocidade, permitindo a organização de campanhas de vacinação ou outras medidas preventivas. Para entender melhor os efeitos da conectividade da paisagem na dispersão do vírus da febre amarela (YFV) no Brasil, usamos uma abordagem de redes e modelamos o movimento de casos de primatas não humanos, as chamadas epizootias, ao longo do tempo. As redes consideraram cada epizootia como um nó, e a dispersão entre os nós como links. Esses links foram estabelecidos considerando, respectivamente, a data de cada epizootia, a distância entre os nós e a permeabilidade da paisagem entre cada par de nós. Nossos resultados demonstraram que a YFV se dispersou em média 1, 42 km/dia, sendo que o maior movimento teve 6, 9 km/dia. As dispersões foram mais longas no verão (1, 2 km/dia) do que no inverno (0, 22 km/dia). A maioria dos movimentos de dispersão ocorreram em até 1 km/dia (71%) e dentro de uma semana após a chegada do vírus no nó de origem (73%), exceto no inverno, onde as dispersões ocorreram dentro de um período de até 20 dias. O melhor modelo indicou que a YFV se dispersa principalmente por estradas adjacentes a áreas florestais, e ao longo das bordas da floresta (que possuem um tamanho de até 100 m de largura) em interface com áreas agrícolas, água e áreas de silvicultura. As áreas urbanas, agrícolas e florestais atuaram como barreiras importantes para o movimento do vírus. Síntese e aplicações . Através de análises de conectividade da paisagem, fornecemos aqui a primeira evidência de que paisagens altamente fragmentadas com uma ampla rede de estradas e grandes densidades de bordas florestais facilitam a propagação do vírus da febre amarela, e que a manutenção de grandes blocos de floresta pode ajudar a inibir esta propagação. Estes resultados podem contribuir para orientar ações de restauração florestal e de manejo da paisagem a fim de ampliar os benefícios à saúde relacionados aos projetos de restauração, além de seus benefícios para a conservação da biodiversidade e para a mitigação das mudanças climáticas.